Nanomolar activity of 4-hydrazinylphenyl benzenesulfonate against breast cancer Michigan Cancer Foundation-7 cell lines - Riska Prasetiawati; Syahrul Hidayat; Adel Zamri; Muchtaridi Muchtaridi (Wolters Kluwer Medknow Publications, 2022)
Hydrazine is an alkaline reduction compound which is widely used in synthesis. Based on the structure-activity analysis, to elicit antitumor activity, the presence of the N-methyl group is an absolute requirement. The aim of the research is to synthesize a new hydrazine derivate compound that has potency as a novel anti-breast cancer. 4-hydrazinylphenyl benzenesulfonate was synthesized employing reduction and diazotization methods. Structure characterization was carried out using Fourier transform infrared (FTIR), C13-nuclear magnetic resonance (NMR), H1-NMR, and High Resolution Time-of-Flight Mass Spectrometry (HR-TOF-MS). The anti-cancer activity of this compound against breast cancer Michigan Cancer Foundation-7 (MCF-7) cell line was determined using a PrestoBlue viability assay. The new of hydrazine derivative, 4-hydrazinylphenyl benzenesulfonate, has been successfully synthesized. The reduction and diazotization methods have been successfully used in the synthesis of new compound of hydrazine derivatives. Structure characterization of 4-hydrazinylphenyl benzenesulfonate was established using FTIR, C13-NMR, H1-NMR, and HR-TOF-MS. The anti-cancer activity of this compound against breast cancer MCF-7 cell line was determined using a PrestoBlue viability assay with IC50 0.00246 μg/mL or 9.32 nM. In conclusion, 4-hydrazinylphenyl benzenesulfonate was successfully synthesized as a new candidate for anti-breast cancer compound.